Non-native molluscan colonizers on deliberately placed shipwrecks in the Florida Keys, with description of a new species of potentially invasive worm-snail (Gastropoda: Vermetidae) - Bieler,Rüdiger; Granados-Cifuentes,Camila; Rawlings,Timothy A.; Sierwald,Petra; Collins,Timothy M. (PeerJ, 2017)
Artificial reefs created by deliberately sinking ships off the coast of the Florida Keys island chain are providing new habitat for marine invertebrates. This newly developing fouling community includes the previously reported invasive orange tube coral Tubastraea coccinea and the non-native giant foam oyster Hyotissa hyotis. New SCUBA-based surveys involving five shipwrecks spanning the upper, middle, and lower Florida Keys, show T. coccinea now also established in the lower Keys and H. hyotis likewise extending to new sites. Two additional mollusks found on the artificial reefs, the amathinid gastropod Cyclothyca pacei and gryphaeid oyster Hyotissa mcgintyi, the latter also common in the natural reef areas, are discussed as potentially non-native. A new species of sessile, suspension-feeding, worm-snail, Thylacodes vandyensis Bieler, Rawlings & Collins n. sp. (Vermetidae), is described from the wreck of the USNS Vandenberg off Key West and discussed as potentially invasive. This new species is compared morphologically and by DNA barcode markers to other known members of the genus, and may be a recent arrival from the Pacific Ocean. Thylacodes vandyensis is polychromatic, with individuals varying in both overall head-foot coloration and mantle margin color pattern. Females brood stalked egg capsules attached to their shell within the confines of their mantle cavity, and give rise to crawl-away juveniles. Such direct-developing species have the demonstrated capacity for colonizing habitats isolated far from their native ranges and establishing rapidly growing founder populations. Vermetid gastropods are common components of the marine fouling community in warm temperate and tropical waters and, as such, have been tagged as potentially invasive or with a high potential to be invasive in the Pacific Ocean. As vermetids can influence coral growth/composition in the Pacific and have been reported serving as intermediate hosts for blood flukes of loggerhead turtles, such new arrivals in the Florida Keys National Marine Sanctuary are of concern. Growing evidence indicates that artificial reefs can act as permanent way-stations for arriving non-natives, providing nurseries within which populations may grow in an environment with reduced competition compared to native habitats. Consequently, artificial reefs can act as sentinels for the appearance of new species. Ongoing monitoring of the developing molluscan fauna on the artificial reefs of the Florida Keys is necessary to recognize new invasions and identify potential eradication targets, thereby assuring the health of the nearby natural barrier reef.
Keywords: Colonization; Diversity; Western Atlantic; Invasive species; Coral reef; Artificial reef; Introductions; Fouling community